Roman Field-System Earthworks in the Birklands and Belhaugh Hays, Nottinghamshire. (November 2017) - Malone, Steve
ABSTRACT: Processing and analysis of LiDAR data in Nottinghamshire has identified the survival of earthwork field-systems beneath woodland in some of the oldest established parts of Sherwood Forest. The morphology and alignment of these field-systems strongly suggest that they represent a survival of the late Iron Age and Roman brickwork-plan field-systems of North Nottinghamshire and South Yorkshire with considerable potential to elucidate the history of abandonment of these fields and the establishment of Sherwood Forest.